Vita, tecnica e senso. La meditación de la técnica di Ortega y Gasset - Giaculli, Fiorella (Mechane, 2022)
The present paper focuses on the definition of technique as outlined in Ortega’s La meditación de la técnica, and examines the relation between this definition and his interpretation of human life as “programa vital”. According to Ortega, both human life and technique have a poietical character: human existence is considered as the production of a project – i.e “pretensión o programa de ser”, in the philosopher’s terms – while the technique constitutes the set of acts, which reforms the “circunstancia” (nature or world), to realise the programs of the “animal fantástico”. By investigating the relation between life and technique, the paper underlines how the right connection between these two terms is fundamental to Ortega. He maintains that the technique should be thought as a function of life and be subordinated to it. The program of life should define and guide the technical acts, and not viceversa, since the limitless and undefinable potentialities of technique could denature the definite essence of life. In gist, according to Ortega, it is essential to make a distinction between “pre-técnico” and “técnica”, hence between the idea of life to achieve, defined as “deseo original”, and the acts to realise it.